1994
DOI: 10.1099/00221287-140-6-1411
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth arrest on carotene accumulation and photosynthesis in Dunaliella

Abstract: The halotolerant green alga Dunaliella bardawil is known to accumulate /3-carotene in response to stress factors such as high light intensity, high salt concentrations and nutrient limitation. In this report, the accumulation of ficarotene was studied in cells from nitrate-limited chemostat cultures, in comparison with those of D. salina, a strain that does not accumulate /3-carotene under stress conditions. D. bardawil responded to growth arrest by accumulating /3-carotene and, to a lesser degree, lutein and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…The continuance in the increase of carotenoids observed in the present study in the algal isolates even after cessation of growth i.e. between 24 -30 days could also be attrib-uted to nutrient depleted conditions [36,37]. This results demonstrates the maximum β-carotene exhibited by all the isolates in last day of the experiment was due to nutrient depleted condition, which have been previously observed in Dunaliella cultivated by Mojaat et al [38].…”
Section: Molecular Identification Of Dunaliella Isolatessupporting
confidence: 69%
See 1 more Smart Citation
“…The continuance in the increase of carotenoids observed in the present study in the algal isolates even after cessation of growth i.e. between 24 -30 days could also be attrib-uted to nutrient depleted conditions [36,37]. This results demonstrates the maximum β-carotene exhibited by all the isolates in last day of the experiment was due to nutrient depleted condition, which have been previously observed in Dunaliella cultivated by Mojaat et al [38].…”
Section: Molecular Identification Of Dunaliella Isolatessupporting
confidence: 69%
“…The observations indicated that the pigments such as Chl a and Chl b were predominant in the growth phase of Dunaliella while the amount of total carotenoids increased and accumulated to high levels in carotenogenic alga during the red orange phase. Maximal carotene accumulation depends upon various factors which include high light intensity [34], extreme temperatures [35], high salinity [35] and deprivation of mineral nutrients including nitrate, sulphate and possibly phosphate [36,37]. The continuance in the increase of carotenoids observed in the present study in the algal isolates even after cessation of growth i.e.…”
Section: Molecular Identification Of Dunaliella Isolatesmentioning
confidence: 77%
“…The halotolerant green alga Dunaliella salina is well known for its b-carotene production (Vorst et al 1994). b-Carotene production in D. salina is enhanced by suboptimal growth conditions such as high light intensity, salinity or temperature (Vorst et al 1994), or nutrient limitation (Marín et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…However, in Ben-Amotz and Avron (1983) and Vorst et al (1994), the D. salina strain they used was not able to accumulate β-carotene. In Gómez and González (2005), they used the same strain as we did.…”
Section: A B C Dmentioning
confidence: 99%
“…Some of Dunaliella strains are well known for the high production of carotenoids, especially β-carotene ). This alga produces large amount of β-carotene under stress conditions such as high light (HL) (Vorst et al 1994, Coesel et al 2008, Lamers et al 2010, high salinity (Vorst et al 1994, Hadi et al 2008, nutrient limitation (Marín et al 1998, Coesel et al 2008, and nitrogen starvation (Sánchez-Estudillo et al 2006, Lamers et al 2012. Ability of Dunaliella to thrive under extreme salinities gives a selective advantage that inhibits growth of other algae and its predators.…”
Section: Introductionmentioning
confidence: 99%